2002
DOI: 10.1207/s15327604jaws0501_3
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Adoption Versus Euthanasia Among Dogs and Cats in a California Animal Shelter

Abstract: The purpose of this retrospective cohort study was to investigate determinants of adoption of cats and dogs from a large municipal animal shelter. The subjects were 4,813 cats and 3,301 dogs impounded by the Sacramento County Department of Animal Care and Regulation and offered for adoption September 9, 1994 to May 26, 1995. The study constructed models predicting the conditional probability of adoption using logistic regression and a final multiple logistic regression model from variables found to be importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
136
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(158 citation statements)
references
References 2 publications
16
136
2
4
Order By: Relevance
“…There was also a bias towards one sex, with males being adopted quicker even though it was the less abundant sex available. This sex preference has been reported before in other studies (Lepper et al, 2002;Fantuzzi et al, 2010). From all the behavioural variables examined, only rub was significantly correlated with the Length of Stay.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There was also a bias towards one sex, with males being adopted quicker even though it was the less abundant sex available. This sex preference has been reported before in other studies (Lepper et al, 2002;Fantuzzi et al, 2010). From all the behavioural variables examined, only rub was significantly correlated with the Length of Stay.…”
Section: Discussionsupporting
confidence: 89%
“…HSUS, 1995;Gourkow, 2001). However, data show that tendency to sit at the front of the pen (Wells and Hepper, 1992) or physical characteristics (such as coat colour or breed: Podberscek and Blackshaw, 1988;Lepper et al, 2002;Delgado et al, 2012;Brown and Morgan, 2015) are the traits that most influence adopters' actual, final decisions (Gourkow and Fraser, 2006). Fantuzzi et al (2010) also found a positive relationship between activity levels, viewing time and adoption decision in shelter cats.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…According to our results, females have demonstrably shorter LOS in shelters compared to male dogs. This finding is supported by several other studies (Patronek et al 1995;Lepper et al 2002;Clevenger and Kass 2003;Marston et al 2004;Mondelli et al 2004;Diesel et al 2007). These studies also showed that females are more likely to be adopted.…”
Section: Discussionsupporting
confidence: 86%
“…puppies up to 1 year of age) have the shortest LOS in shelters. This finding is confirmed by one Czech study (Němcová and Novák 2003) and also by many other studies (Patronek et al 1995;Hart et al 1998;Lepper et al 2002;Previde et al 2003;Brown et al 2013). Brown et al (2013) also found that LOS did not depend on other factors such as the size of the puppy, sex, or breed group.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation